Multidisciplinary team collaboration impact on NGF, BDNF, serum IGF-1, and life quality in patients with hemiplegia after stroke: NGF, BDNF, serum IGF-1, and life quality - He, Jing; Chen, Lanlan; Tang, Fan; Huang, Rui; Liao, Jingting; Tian, Hua (Cellular and Molecular Biology, 2023)
This study aimed to study the impact of multidisciplinary team collaboration on NGF, BDNF, serum IGF-1, and life quality in patients with hemiplegia after stroke. For this purpose, 200 post-stroke hemiplegic patients admitted from March 2022 to February 2023 were selected and randomly divided into a control group (100) and an observation group (100). The control group was given routine nursing care, while the observation group was given a multidisciplinary team collaboration model. The neurotroph in [nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1 (IGF-1)] and nutritional status [hemoglobin (HGB), serum albumin (ALB), transferrin (TRF)] of patients were compared before and after the intervention on the second day of admission and on the 30th day of intervention. The FUGL Meyer (FM) motor function assessment scale, NIHSS National Institutes of Health Stroke Scale, and the Specialized Quality of Life Scale (SS-QIL) for stroke patients were used to assess limb motor function, balance function, degree of neurological impairment, and life quality. Results showed that before intervention, there was no statistically significant difference in the levels of NGF, BDNF, IGF-1, HGB, ALB, TRF, limb motor function, balance function, neurological deficits, and quality of life scores between the two (P>0.05); After intervention, the levels of NGF, BDNF, IGF-1, HGB, ALB, and TRF in the observation group were significantly higher (P<0.05); The FM and SS-QOL of patients in the observation group were significantly higher (P<0.05); The NIHSS score of patients in the observation group was significantly lower (P<0.05). In conclusion, multidisciplinary team cooperation can significantly improve the level of neurotrophin, reduce the degree of nerve defect, and promote the recovery of limb function, balance function and life quality for stroke patients with hemiplegia.